Acute Promyelocytic Leukemia: Clinico-Demographic Profile - Altaf, Nadia (International Journal of Pathology, 2019)
Acute promyelocytic leukemia is a unique subtype of acute Myeloid Leukemia about which there is limited data from Pakistan. The aim of the present study is to evaluate itsclinico-demographic profile along with risk stratification at a tertiary care hospital in Pakistan. Materials and Methods: A retrospective study was performed in which 28 cases of acute promyelocytic leukemia diagnosed at Pathology department of Hayatabad Medical Complex Peshawar, Pakistan between June 2014 and July 2018 were enrolled for analysis. All data were documented and statistical analysis was performed by SPSS-23 software. Results: Median age of the patients was 21 (range 2-65) years. Male to female ratio was3:1 .Hypergranular variant (92.8%) was more common as compared to microgranular type (7.14%). Majority of patients had complaints of fever (71.4%), bleeding (53.5%) and generalized weakness (14.2%). Pallor (64.2%) was the predominant finding on physical examination followed by petechial and purpureal rashes (46.4%). Mean Hemoglobin was 8.3 (range 5.3-12.2) g/dl. The mean total leukocytes count was 39.6 (range 1.3-121) x 109/ Land mean platelet count was 40 (range 7-78) x 109 /L. Most patients fall into high riskgroup (60.7%) on risk stratification followed by intermediate risk (32.1%) and low risk (7.1%). Conclusion: Clinical features and risk stratification results of our study are comparable with the published data.In the present study pallor was the most commonpresentation. Risk stratification showedpredominance of high-risk score.